Evidence for dysregulation of axonal growth and guidance in the etiology of ASD - McFadden, Kathryn; Minshew, Nancy (Frontiers in Human Neuroscience, 2013)
Current theories concerning the cause of autism spectrum disorders (ASDs) have converged on the concept of abnormal development of brain connectivity. This concept is supported by accumulating evidence from functional imaging, DTI, and high definition fiber tracking (HDFT) studies which suggest altered microstructure in the axonal tracts connecting cortical areas may underly many of the cognitive manifestations of ASD. Additionally, large-scale genomic studies implicate numerous gene candidates known or suspected to mediate neuritic outgrowth and axonal guidance in fetal and perinatal life. Neuropathological observations in postmortem ASD brain samples further support this model and include subtle disturbances of cortical lamination and subcortical axonal morphology. Of note is the relatively common finding of poor differentiation of the gray-white junction associated with an excess superficial white matter or “interstitial” neurons (INs). INs are thought to be remnants of the fetal subplate, a transient structure which plays a key role in the guidance and morphogenesis of thalamocortical and cortico-cortical connections and the organization of cortical columnar architecture. While not discounting the importance of synaptic dysfunction in the etiology of ASD, this paper will briefly review the cortical abnormalities and genetic evidence supporting a model of dysregulated axonal growth and guidance as key developmental processes underlying the clinical manifestations of ASD.